2006
DOI: 10.1111/j.1399-3054.2006.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tolerance to ozone and drought stresses in transgenic tobacco overexpressing dehydroascorbate reductase in cytosol

Abstract: Ascorbate (vitamin C) is a potent antioxidant protecting plants against oxidative damage imposed by environmental stresses such as ozone and drought. Dehydroascorbate reductase (DHAR; EC 1.8.5.1) is one of the two important enzymes functioning in the regeneration of ascorbate (AsA). To examine the protective role of DHAR against oxidative stress, we developed transgenic tobacco plants overexpressing cytosolic DHAR gene from Arabidopsis thaliana. Incorporation of the transgene in the genome of tobacco plants wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
113
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(130 citation statements)
references
References 44 publications
14
113
1
1
Order By: Relevance
“…DHA undergoes irreversible hydrolysis to 2, 3-diketogulonic acid or is recycled to AsA by DHAR, thereby capturing AsA before it lost. Recent studies showed that both MDHAR and DHAR are equally important in regulating AsA levels and its redox state under oxidative stress condition (Eltayeb et al 2006(Eltayeb et al , 2007Wang et al 2010;Shalata et al 2001). Results obtained in this study showed that both MDHAR and DHAR decreased along with a decreased level of AsA (Figs.…”
Section: Discussionsupporting
confidence: 57%
“…DHA undergoes irreversible hydrolysis to 2, 3-diketogulonic acid or is recycled to AsA by DHAR, thereby capturing AsA before it lost. Recent studies showed that both MDHAR and DHAR are equally important in regulating AsA levels and its redox state under oxidative stress condition (Eltayeb et al 2006(Eltayeb et al , 2007Wang et al 2010;Shalata et al 2001). Results obtained in this study showed that both MDHAR and DHAR decreased along with a decreased level of AsA (Figs.…”
Section: Discussionsupporting
confidence: 57%
“…Among antioxidative enzymes, DHAR overexpression represents a reliable approach to confer enhanced tolerance to multiple environmental stresses such as ozone, drought, slat and aluminum stresses (Eltayeb et al 2006, Yin et al 2010. In the present study, we report the generation of transgenic potato overexpressing AtDHAR1, the metabolic effects of DHAR overproduction on the AsA pool, and the resulting gain in stress tolerance against the herbicide methylviologen (MV) and against drought and salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Immunodetection was performed using diluted (1 : 10 000) guinea pig antibodies against the DHAR protein (Eltayeb et al 2006) as the first antibody and a diluted (1 : 5000) horseradish peroxidase-conjugated anti-guinea pig IgG (Sigma) as the second antibody. Chemiluminescent detection was carried out using Immobilon Western Chemiluminescent HRP Substrate (Millipore, Tokyo, Japan), and the signals were visualized using the LAS-4000 Mini (Fujifilm, Tokyo, Japan).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations